A study on attitude of university academia towards the use of open educational resources in higher education - Irshad Hussain; Jawed Hassan Chandio; Riaz Hussain Khan Sindher (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The present study was conducted with the objectives a). to evaluating general perception of university academia about using open educational resources (OERs) in higher education; b). to examining the attitude of university academia towards the use of OER in enhancing academic, research and learning pursuance; and c). to identifying problems challenges of university academia in using OERs in higher education. The population of the study consists of university teachers (total 556) of the Islamia University of Bahawalpur, Pakistan. The sample of the study comprises of 278 (50%) of the population. The survey was undertaken through informed consent of the respondents and the respondents participated voluntarily in the survey; however, the response rate was calculated to be 91% as 253 of the respondents completed the survey. The survey adopted a mixed (quantitative and qualitative) approach of data collection. Therefore, two research tools were prepared for data collection. A questionnaire was prepared on fivepoint rating Likert scale for collecting quantitative data whereas; an interview protocol was prepared for qualitative data collection. The calculated reliability of (Cronbach's alpha) was 0.805 indicating a high level of internal consistency for the tool with specific sample under study. The interview protocol was finalized through expert opinion. The finalized research tools were administered personally by the researcher -questionnaire was administered on 278 respondents with 91% response rate. Besides it, qualitative data were collected from 58 respondents by using focused group interview technique through an interview protocol. The researcher coded quantitative data in Ms-Excel program and analyzed it through mean scores and percentage; whereas the qualitative data were analyzed by grouping the themes. The qualitative and quantitative data analysis revealed that university academia acknowledged the use of OERs in promoting higher education in Pakistan. They affirmed that OERs facilitated them in conducting research, accessing to instructional materials and learning about innovations and developments in their respective disciplines. They were of the view that OERs were freely available to them and provided access to extensive body of knowledge, latest research practices and instructional experiences. However, they faced some technology related problems in accessing to OERs. These problems included bandwidth of internet, intermittent electricity failure, bugs and computer viruses; and finger's joint pains, backache, headache and computer vision syndrome.
Keywords: 330; open educational resources; research pursuance; academic hub; information and communication technologies; computer vision syndrome; open access